Analisis Media Pembelajaran Bahasa Arab Berbasis TPACK di SMA Muhammadiyah 2 Sidoarjo - Fithriyani Churriyatul Ummah; Khizanatul Hikmah (Universitas Muhammadiyah Gorontalo, 2025)
Through this study, the researcher wants to find out the readiness of teachers in integrating TPACK-based technology media, the use of technology media to explore Arabic learning materials, and learning media designed or developed by teachers. The researcher uses a qualitative method with a descriptive approach. Data was obtained through interviews, as well as photo documentation. The result of this research is that teachers are required to be ready to adapt to technological media. The application of the right learning media can increase students' enthusiasm, trigger healthy competition, and create self-awareness to ask for remidial if the score is low. One of the things that is considered in choosing technology media is that it is simple and easy so that teachers and students can use it. There are various kinds of media designed or developed by teachers, including Canva, Socrative, Comika. A teacher needs to continue learning, monitor technological developments, and be close to students so that they can be more up to date about technology that can be integrated into learning.